The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.ejmg.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation that mutations in DDX59 cause an autosomal recessive form of oral-facial-digital syndrome: Further delineation of the DDX59 phenotype in two new families

Abstract: We report three probands from two unrelated consanguineous families of South Asian origin who all carry the same rare novel homozygous variant within the dead box helicase gene DDX59 in association with features of oral-facial-digital syndrome (OFDS). DDX59 variants have been reported previously in an unclassified, autosomal recessive form of OFDS; clinically associated with features including tongue lobulation, cleft palate, frontal bossing, hypertelorism and postaxial polydactyly. All three probands had lobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…LoF variants in another member of this helicase family, DDX59, have also been reported to cause an autosomal-recessive form of ID with features of oral-facial-digital syndrome. [53][54][55] Interestingly, the phenotypic traits observed in our DDX6 cohort align well with the syndromes described in individuals with pathogenic variants in DDX3X and DHX30. [50][51][52] These include ID, DD, gait abnormalities, cardiac anomalies, and corpus callosum hypoplasia, as well as dysmorphic facial features (high forehead, a bulbous nasal tip, hypertelorism, and arched eyebrows).…”
Section: Discussionsupporting
confidence: 79%
“…LoF variants in another member of this helicase family, DDX59, have also been reported to cause an autosomal-recessive form of ID with features of oral-facial-digital syndrome. [53][54][55] Interestingly, the phenotypic traits observed in our DDX6 cohort align well with the syndromes described in individuals with pathogenic variants in DDX3X and DHX30. [50][51][52] These include ID, DD, gait abnormalities, cardiac anomalies, and corpus callosum hypoplasia, as well as dysmorphic facial features (high forehead, a bulbous nasal tip, hypertelorism, and arched eyebrows).…”
Section: Discussionsupporting
confidence: 79%
“…They both presented small OFC since birth, similarly to the patients recently reported by Faily et al. (). Proband II.1 presented since early adulthood diffuse white matter signal abnormalities associated with subcortical ischemic changes, Proband II.2 showed brain MRI features similar to her brother and EMG features of mild peripheral (axonal) neuropathy.…”
supporting
confidence: 86%
“…() were missense variants (c.1100T > G: p.Val367Gly; c.1600G > A: p.Gly534Arg) and the mutation recently described by Faily et al. () affected a stop codon (c.1859G > T: p.*620Leuext*22) extending the protein product, whereas the homozygous mutation we identified in the present study lead to an early truncation of the protein, likely explaining the more severe phenotype including the complex heterogeneous neurological involvement. Interestingly, our functional analysis of the Drosophila model clearly showed that mahe null embryos exhibit highly disorganized neuron clusters and axonal projections, loss or incomplete ventral nerve cord, and also show shortened lifespan.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…So far, 8 causative genes have been identified for OFD syndrome [57,58]. Among these genes, TCTN3 is also reported to be a causative gene of OFD syndrome.…”
Section: : the Role Of Tectonic Proteins In Ciliopathiesmentioning
confidence: 99%